Un bordado heráldico de María de Padilla: Propuestas de identificación. - Francisco Olmos, Jose Maria de (Eikón / Imago, 2025)
Heraldic elements are a very important source for the identification and dating of official documents, such as coins or seals, or of artistic pieces, be they tombs, monuments, furniture, clothing, etc. But sometimes we have identification problems that require a more precise study, as in the case of the heraldic embroidery attributed to María de Padilla that is in the Textile Museum of Tarrasa and whose origin is in the monastery of Santa Clara de Astudillo. In this work we are going to question the traditional identifications of the shields that appear in it and we are going to propose new attributions through comparative heraldry studies.